A CRITICAL APPROACH TO THE TRANSLATIONS OF NEBE 78/33. VERSE - Yahya YAŞAR (Fırat University, 2021)
The science of tafsir tries to determine the meaning of the words as much as possible by analyzing the words of the Quran linguistically. The mufassırs present their comments or analyzes as data for understanding the Quran. People who translate use these data to capture the meaning of the words. However, translation is a more sensitive work that requires careful analysis of all this data. Instead of making literal translation based on meanings of the words, the true meaning behind these words must be captured. In some translations of Nebe 78/33, the word "kevâ‘ib"  is translated with expressions such as "Girls with budded breasts", "Young girls with breasts". However, the Quran conveyed such subjects in a unique style. Those who translated the Quran should have reflected this style in their translations as much as possible, but it seems that this was not done. In some other translations, it is translated with general concepts that include male and female gender as "perfectly harmonious wonderful spouses", "equally attractive wives" “Citrus-breasted young dilbers”. However, in the Arabic language, "ka'ib / ku'ub / kevâ‘ib" patterns are only words that describe the female gender. It can be said that both translations are erroneous. In the first, a mistake was made due to using the literal meaning of the word. In the second example the mistake is made  by disconnecting the word from its  etymological meaning. In this study, the mentioned translations are being analyzed in terms of linguistic, integrity and stylistic features of the Quran. It is being aimed to contribute to the translation studies to be carried out from now on by mentioning the translations which are thought to be correct and accurate.